Ultrafast dissociative ionization and large-amplitude vibrational wave packet dynamics of strong-field-ionized di-iodomethane - Wei, Zhengrong (2020)
We employ few-cycle pulses to strong-field-ionize di-iodomethane (CH2I2) and femtosecond extreme ultraviolet (XUV) transient absorption spectroscopy to investigate the subsequent ultrafast dissociative ionization and vibrational wave packet dynamics. Probing in the spectral region of the I 4d core-level transitions, the time-resolved XUV differential absorption spectra reveal the population of several electronic states of CH2I2+ by strong-field ionization. Global analysis reveals three distinct time scales for the observed dynamics: 20 ± 2 fs, 49 ± 6 fs, and 157 ± 9 fs, ascribed to relaxation of the CH2I2+ parent ion from the Franck-Condon region, dissociation of high-lying excited states of CH2I2+ to I+ (3P2), CH2I, and I2+ (2Π3/2,g), and dissociation of CH2I2+ to I (2P3/2) and CH2I+, respectively. Oscillatory features in the time-resolved XUV differential absorption spectra point to the generation of vibrational wave packets in both the residual CH2I2 and the CH2I2+ parent ion. Analysis of the oscillation frequencies and phases reveals, in the case of neutral CH2I2, C-I symmetric stretching induced by bond softening and I-C-I bending driven by a combination of bond softening and R-selective depletion. In the case of CH2I2+, both the fundamental and first overtone frequencies of the I-C-I bending mode are observed, indicating large-amplitude I-C-I bending motion, in good agreement with results obtained from ab initio simulations of the XUV transition energy along the I-C-I bend coordinate. These results show that femtosecond XUV absorption spectroscopy is well-suited for studying ultrafast photodissociation and vibrational wave packet dynamics.